Relevance of self-rated health level and mental health in Korean adolescents - Yunjeong Kim; Joohee Shim (Frontiers in Public Health)
IntroductionIn this study, we explored the impact of mental health on self-rated health of Korean adolescents. By examining the relationship between self-assessed health and mental-health issues, such as anxiety and depression, this study sought to inform strategies for enhancing health education and school-based interventions.MethodsSecondary data from the Korea National Health and Nutrition Examination Survey were analyzed, with a sample comprising 418 middle and high school students. The study examined general characteristics of the sample and the correlations between subjective health status and mental-health indicators and between subjective health status and physical activity levels. Frequency and cross-tabulation analyses were performed to explore these relationships. Logistic regression analysis was conducted to identify factors influencing subjective health status. Statistical significance was set at p < 0.05.ResultsAssociations were noted between subjective health status and mental-health indicators, including stress recognition (p < 0.05), suicidal ideation in the past year (p < 0.001), suicide planning in the past year (p < 0.001), suicide attempts in the past year (p < 0.001), and counseling for mental-health problems in the past year (p < 0.005). Additionally, subjective health status was correlated with the following physical activity metrics: average daily hours spent seated (p < 0.05) and engagement in physical activities lasting 1 h or more per day (p < 0.1). Several factors were identified to influence subjective health status including the frequency of breakfast consumption per week (p < 0.05) and suicidal ideation in the past 1 year (p < 0.05).DiscussionThe study findings highlight the considerable effects of mental health and health behaviors on adolescents’ subjective health status. Thus, addressing school health should go beyond promoting physical health alone. An environment that supports adolescents’ mental and social well-being, enabling them to grow into healthy adults, is necessary.